Perceptions of environmental education among senior Ciskeian educationists, and the implications for educational change in the Ciskei region - Mkala-Pholo, Pumla Patricia (Rhodes University, Faculty of Education, Department of Education, 1994)
This study was conducted to investigate perceptions of Environmental Education among senior Ciskeian educationists, and to explore the possibility of implementing Environmental Education in school and college curricula in the Ciskei region. Data was collected from interviews with a sample of senior Ciskeian educationists, then analysed and assessed. Corroborating information was obtained from attendance at several regional workshops organised by the Environmental Education Policy Initiative. The data indicated a sound general awareness of environmental problems in Ciskei and a belief in Environmental Education as a means toward their solution. Although the interviewees' understanding of Environmental Education was imperfect, there was broad support for its aims and principles. Since the study was motivated by concern about the implementation of Environmental Education in Ciskei, the results obtained were encouraging.
Keywords: Environmental education -- South Africa -- Ciskei; Environmental education -- Curricula -- South Africa -- Ciskei; Educators -- South Africa -- Ciskei -- Attitudes; Educational planning -- South Africa -- Ciskei